«Етимологічний словник суфіксів української мови» — новий етап у слов’янській компаративістиці - Лучик, В.В. (Мовознавство, 2013)
Укладання «Етимологічного словника суфіксів української мови» — об’єктивно зумовлене явище, яке започаткує новий етап у розвитку української, слов’янської та індоєвропейської компаративістики, адже ці важливі для з’ясування походження, історичної семантики і структури слів афікси зазвичай не потрапляли до традиційних етимологічних словників лексем. The peak of development of comparative studies is creation of etymological dictionaries, which
nowadays are present in the majority of Slavic languages. Compilation of etymological dictionaries
of suffixes of national languages is supposed to become a new stage of Slavic comparative historical
lexicography since these affixes, being important for understanding of the origin of words, usually
have been not included in traditional etymological dictionaries.
P. Skok explained for the first time the etymology of suffixes of Serbian and Croatian in 4-volume
etymological dictionary of aforementioned languages (1971-1974), which was compiled
by him. F. Slavsky explained the etymology of Common Slavic suffixes in the foreword to the first
three volumes of Common Slavic dictionary (1974—1979). However, these works do not cover all
Common Slavic and the majority of suffixes of separate Slavic languages that were developed in the
later stages, which means that creation of full etymological dictionaries of suffixes of national languages
is urgent.
The idea of creation of «Etymological Dictionary of Suffixes of Ukrainian» was suggested
by O. O. Potebnya Institute of Linguistics of National Academy of Sciences of Ukraine. At the moment
the Department of General Slavic Problematic and East Slavic Languages finishes its work on
this dictionary. Its creation was related to overcoming several problems: 1) absence in Slavic and
world lexicography of dictionaries of such a kind; 2) different levels of exploration of the structure,
derivative meanings, and origin of suffixes in different Slavic languages; 3) problematic reconstruction
of original semantics of suffixes, which is stipulated by abstract meaning of these morphemes;
4) complexity of determining formal structure of suffixes, which underwent significant historical
changes in the development process; 5) absence of clear criteria that determine source language of
suffixes, intermediary, and direction of their spreading from one language to another; 6) complexity
of differentiating polysemy and homonymy of suffixes; 7) different interpretation of suffixes,
invariants, variants of suffixes, and suffixoids in scientific literature.
Publication of «Etymological
Dictionary of Suffixes of Ukrainian» is a phenomenon which was caused by objective reasons. It
starts a new phase of development of Slavic and Indo-European comparative studies, which remain
one of the main areas of modem linguistics.